Influence of product quality and price on the decision to purchase eyesglass at Optic Naufal Serpong - Muhammad Arif Ramdani; Novia Susanti (Central Research Institute for Agriculture (CeRIA), 2023)
This study aims to examine the effect of Product Quality and Price on Purchasing Decisions at Naufal Optics in Serpong. Types of quantitative research methods with an associative approach, with a population of 990 consumers and with a sample of 91 respondents and with analysis using analytical tests, namely validity tests, reality tests, linear regression tests, correlation coefficient tests, determination tests, t tests and f tests also use classical tests normality tests, multicollinearity tests, autocorrelation tests and heteroscedasticity tests. The results of the research conducted. the effect of Product Quality on Purchasing Decisions obtained the value of the regression equation Y = 1.048 + 0.613 X1. The hypothesis test obtained a calculated value of ttable > (21,328>1,987). Thus, Ho was rejected and H1 was accepted, this shows that there is a positive and partially significant influence between Product Quality and Purchasing Decisions at Naufal Optics in Serpong. While the Price against the Purchase Decision obtained the value of the regression equation 2.235 + 0.923 X1. Test the hypothesis obtained tcalculate ttable value or (23,253> 1,987). Thus Ho was rejected and H2 was accepted, this shows that there is a partial positive and significant influence between Price and Purchase Decision at Naufal Optics in Serpong. then, the effect of Product Quality and Price on Purchasing Decisions obtained regression equation Y = 0.318 + 0.273 X1 + 0.551 X2. The hypothesis test obtained the value of Fcalculate > Ftable or (339,260 > 3.10). Thus, Ho is rejected and H3 is accepted, meaning that there is a simultaneous positive and significant influence between Product Quality and Price on Purchasing Decisions at Naufal Optics in Serpong.